Development, feasibility, and efficacy of a customized exercise device to deliver intradialytic resistance training in patients with end stage renal disease: Non‐randomized controlled crossover trial. Issue 4 (9th June 2016) - Chan, Danwin; Green, Simon; Fiatarone Singh, Maria; Barnard, Robert; Cheema, Birinder S.
Abstract: Introduction This study assessed the feasibility and efficacy of a novel resistance training device used within an intradialytic progressive resistance training (PRT) intervention. Methods Non‐randomized, within‐subjects crossover design with outcomes assessed at baseline (week 0), postcontrol (week 13) and post‐PRT intervention (week 26). Twenty‐two hemodialysis patients (59% men, 71 ± 11 years) performed PRT three sessions per week for 12 weeks. The resistance training device was developed to enable the performance of 2 upper body and 3 lower body exercises, unilaterally and bilaterally, both before and during dialysis, with loads of 2.5 to 59 kg. Feasibility outcomes included adverse events, adherence and training load progression. Changes in upper and lower body muscular strength, six‐minute walk, aspects of health‐related quality of life (HRQoL) and depression were evaluated. Findings The PRT intervention was delivered without serious adverse events, resulted in 71.2% ± 23.3% adherence and significant adaptation of all training loads from pre to mid to post training (83.8%–185.6%, all P < 0.05). Lower body strength (P < 0.001) and HRQoL subscales (Role‐Physical, Social Functioning, Role‐Emotional) significantly increased (all P < 0.01) and a trend toward reduced depression was noted (P = 0.06). No significant changes were noted in other outcomes. Discussion PRT using the novel resistance training device was feasible and improved measures of physical and psychological health. This device can be utilized in most dialysis centers. Future studies are required to evaluate dose‐response effects of PRT prescriptions in subpopulations, and the translation of PRT to standard dialysis practice.